PENERAPAN ANALISA SWOT DALAM RANCANG BANGUN APLIKASI PENJUALAN TOKO MAINAN ANAK BERBASIS WEB - Lela Nurlaela; Usanto Usanto; Sutrisno Sutrisno (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
The birth and rapid development of the internet into one of the cheapest communication infrastructures and, a wide acceptance rate. By bringing the advantages of the internet such as 24-hour service, access from all directions at a relatively low cost, and other conveniences. Golfy Toys Store is a toy store that only markets via offline marketing by making banners and other offline marketing tools. The process of selling goods is usually still written in the sales book. This affects the revenue earned. A sales system is needed, namely a system that can help speed up the process of making notes that are already automatic, so they don't need to be written on books. The results with this website-based sales system are to help stores improve store branding and provide added value in business models that will strengthen the competitive value of their business in the future amid intense competition with shops selling similar products.